THE DEVELOPMENT STRATEGY OF INDONESIAN NAVAL HUMAN RESOURCES UNIT (LAPETAL) USING SWOT ANALYSIS - Cahyanto Cahyanto; Suparno Suparno; Adi Bandono (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT Quality human resources who are in the Indonesian Navy organization have a very important role. Because with the Indonesian Naval Main Weapon System (Alutsista) award, which is getting more and more sophisticated and the challenges in the era of the industrial revolution 4.0, it is hoped that its human resources will be able to reliably manage the defense equipment. In looking for quality human resources, good planning is needed to achieve optimal organizational goals in the utilization of existing resources. The provision of quality human resources in the Indonesian Navy requires a qualified organization, in this case, is carried out by the Lapetal. So that we need a strategy to develop the Indonesian Naval Human Resources unit. The purpose of this study was to obtain the factors, criteria, and formulation of development strategies. This study uses the SWOT analysis method. Based on the SWOT analysis, there were 10 criteria for internal factors and 7 criteria for external factors as well as 4 alternative strategies, namely 7 SO strategy steps, 5 ST strategy steps, 6 WO strategy steps and 4 WT strategy steps, WO strategy was chosen as the first alternative with the highest weight of 4, 01. Keywords: The Indonesian Naval Human Resources Unit (Lapetal), SWOT Analysis.